Compliance, noncompliance strategies, and the correlates of compliance in 5-year-old japanese and american children - Abe, Jo Ann A; Izard, Carroll E (Social Development, 1999)
The present study compared compliance, noncompliance strategies, and the correlates in 5-year old Japanese and American children were observed during three standardized laboratory procedures. Compliance, noncompliance strategies, and negative affect were coded during Toy Pick Up procedure. Maternal directiveness and mother-directed behaviors were coded during Mother-Child play and Free-play procedures, respectively. A baseline level of play was also obtained during the Free Play procedures to ensure that the children's willingness to engage in the Toy Pick Up procedure would not be confounded with their level of involvement with the toys. Consistent with predictions derived from a review of cross-cultural research on socialization practices, Japanese children showed longer latencies to begin picking up toys in response to maternal requests and were also more likely to engage in the `less skilled' noncompliance strategies of direct defiance and passive noncompliance than American children. The two groups of children did not, however, differ in their level of negative affect during the Toy Pick Up procedure. Contrary to expectations, maternal directiveness was not associated with compliance in either group of children. However, approach behavior to mother during Free Play was inversely correlated with compliance in Japanese, but not American children.
Keywords: Compliance; Cross-cultural; Preschool children; Self-regulation; dept.psy